A NEW RAMPED PYROXIDATION/COMBUSTION FACILITY AT 14CHRONO, BELFAST: SETUP DESCRIPTION AND INITIAL RESULTS. Issue 4 (28th August 2021) - Keaveney, Evelyn M; Barrett, Gerard T; Allen, Kerry; Reimer, Paula J
ABSTRACT: The Belfast Ramped Pyroxidation/Combustion (RPO/RC) facility was established at the 14 CHRONO Centre (Queen's University Belfast). The facility was created to provide targeted analysis of bulk material for refined chronological analysis and carbon source attribution for a range of sample types. Here we report initial RPO results, principally on background material, but also including secondary standards that are routinely analyzed at 14 CHRONO. A description of our setup, methodology, and background (blank) correction method for the system are provided. The backgrounds (anthracite, spar calcite, Pargas marble) reported by the system are in excess of 35, 000 14 C years BP with a mean age of 39, 345 14 C years BP (1σ = 36, 497–43, 800 years BP, N=44) with F 14 C = 0.0075 ± 0.0032. Initial results for standards are also in good agreement with consensus values: TIRI-B pine radiocarbon age = 4482 ± 47 years BP (N=13, consensus = 4508 years BP); IAEA-C6 ANU Sucrose F 14 C= 1.5036 ± 0.0034 (N=10, consensus F 14 C = 1.503). These initial tests have allowed problematic issues to be identified and improvements made for future analyses.